Queer twin cities (University of Minnesota Press, 2010)
The Twin Cities is home to one of the largest and most vital GLBT populations in the nation-and one of the highest percentages of gay residents in the country. Drawn from the pioneering work of the Twin Cities GLBT Oral History Project-a collective organization of students, scholars, and activists devoted to documenting and interpreting the lives of GLBT people in Minneapolis and St. Paul- Queer Twin Cities is a uniquely critical collection of essays on Minnesota's vibrant queer communities, past and present. A rich blend of oral history, archival research, and ethnography, Queer Twin Cities u.